Assessment of factors influencing utilization and conservation of forest resources in Kipini Division of Tana Delta District, Kenya - Olunga M.A; Kavoi M.M; Guthiga P.M (African Journal of Environmental Economics and Management, 2015)
Forest resource utilization poses a challenge to the balance between fragile ecosystems and impoverished populations. As population increases, the demand for forest resources and the resultant degradation are expected to increase. Many benefits can be derived from conservation initiatives. Yet incidences of destruction by local communities are prevalent. This study examined the factors that influence utilization of forest products and attitudes of households towards conservation. The Logit and Negative binomial models were used for analysis. Descriptive and factor analysis were used to assess the attitudes towards conservation. Data was collected from 150 households in Kipini Division of Tana Delta District, Kenya. Logit model results showed that income, distance to the main road, management regime and occupation of the household head influence use of forest products. Results from Negative Binomial regression showed that intensity of use of forest products is influenced by the management regime, occupation of household head, income and distance to the main road. The results of the descriptive and factor analysis indicated that the local community has negative attitude towards conservation of forests. These findings imply that conservation can be enhanced by creating awareness of forest benefits to the community and training them on energy saving charcoal burners.